The effectiveness of napier harvesting machine in reducing postural risk among napier harvesters in Perlis - Mohd Khairul Faizi Abd Rahman (School of Mechatronic Engineering, Universiti Malaysia Perlis, 2015)
The objective of this project is to identify proper working posture thus to design the Napier harvesting ergonomics engineering intervention in order to replace the use of machetes in conventional harvest. The comprehensive laboratory studies were conducted by focusing on stooped posture by using electromyography (EMG).